Peran Penjaga Perdamaian Wanita dalam Proses Bina-Damai: Studi Kasus Operasi Perdamaian Monusco - Satwika Paramasatya (Global South Review, 2015)
Peacekeeping Operations (PKO) is known as an instrument used by the United Nations to create peace in countries affected by conflict. Peacekeeping operations work as a mediator for the parties of the conflict and to ensure that violence no longer exists in the peace process. Once peace is achieved, peace operations are expected to remain involved in the peace building process. At first, men played a very dominant role in peacekeeping operations. Even so, women have been more involved in peace operations nowadays. It can be seen from the increasing number of female members of peacekeeping operations. This paper will discuss the role of women in contributing to the peace building process that occur in the MONUSCO operation in Congo. Congo was chosen because MONUSCO has the highest female members compared to other peacekeeping operations. The research was conducted by using explanatory method to analyze the role of women in peacekeeping operation using parameters such as the implementation of the mandate, the consistency of the implementation of Capstone Doctrine, DDR (Disarmament, demobilization, Reintegration), and CIMIC (Civil-Military Cooperation). The result indicated that women tend to have positive influences towards peace building process in peacekeeping operations judging from the fulfillment of the mandate and the implementation of programs that support the peacekeeping operation itself.